Penyelesaian Sengketa Pilkada Setelah Putusan Mahkamah Konstitusi Nomor 97/PUU-XI/2013 - Nazriyah, R. (Jurnal Konstitusi, 2015)
The problem to be studied in this paper is which body has the authority to resolve election disputes after the decision of the Constitutional Court? What  are the considerations that the court overturned its own authority to resolve dispute elections? Based on the results of analysis it can be concluded that; first, based on the decision No. 97 / PUU-XI / 2013 of the Constitutional Court, it is considered that, “... the legislators are also able to determine that direct elections were not part of  the formal Election as mentioned in section 22E of the 1945 Constitution. So that the dispute of the result is determined as an additional authority of the Supreme Court .. . “The second, the most appropriate agency to handle election disputes is the Supreme Court, which then delegates to the High Court in each region. If litigants are not satisfied with the decision of the High Court, they may appeal to  the Supreme Court. Meanwhile, Law No. 1 2015 About Election of governors, regents, and mayors, was handed over to the Constitutional Court (although temporary) to resolve the election disputes. Therefore, it is immediate to establish regulations particularly the governing competent institution to resolve election disputes.